1999
DOI: 10.1093/emboj/18.8.2127
|View full text |Cite
|
Sign up to set email alerts
|

Fetal liver development requires a paracrine action of oncostatin M through the gp130 signal transducer

Abstract: Fetal liver, the major site of hematopoiesis during embryonic development, acquires additional various metabolic functions near birth. Although liver development has been characterized biologically as consisting of several distinct steps, the molecular events accompanying this process are just beginning to be characterized. In this study, we have established a novel culture system of fetal murine hepatocytes and investigated factors required for development of hepatocytes. We found that oncostatin M (OSM), an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
352
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(367 citation statements)
references
References 64 publications
14
352
0
1
Order By: Relevance
“…Furthermore, the combination of Dex and oncostatin M (OSM), an IL-6 family cytokine, has been shown to be important for the maturation of mice hepatoblasts in vitro. 13,14 Thus, we studied the effect of Dex and various cytokines on the recovery of hepatocytic phenotypes in our in vitro model, and found that both OSM and IL-6 could cause the mature hepatocytic phenotypes if used in combination with Dex. Our results indicate that the ductular transdifferentiation of hepatocytes is reversible and provide insights into the mutual phenotypic plasticity between hepatocytes and bile ductular cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the combination of Dex and oncostatin M (OSM), an IL-6 family cytokine, has been shown to be important for the maturation of mice hepatoblasts in vitro. 13,14 Thus, we studied the effect of Dex and various cytokines on the recovery of hepatocytic phenotypes in our in vitro model, and found that both OSM and IL-6 could cause the mature hepatocytic phenotypes if used in combination with Dex. Our results indicate that the ductular transdifferentiation of hepatocytes is reversible and provide insights into the mutual phenotypic plasticity between hepatocytes and bile ductular cells.…”
Section: Introductionmentioning
confidence: 99%
“…Binding of OSM to its receptor complex (gp130-OSMRb) triggers the activation of two main pathways: the JAK-signal transducer and activator of transcription (STAT) (with STAT1, STAT3 and STAT5) and the mitogen-activated protein kinase (with extracellular signal-regulated kinase (ERK)½) signaling pathways (Auguste et al, 1997;Chen and Benveniste, 2004). Like other IL-6 type cytokines, OSM plays a crucial role in inflammation, immune response, hematopoiesis, liver and neuronal regeneration (Kamiya et al, 1999;Chen and Benveniste, 2004). Specific effects of OSM include the renal inflammatory response (Baumann et al, 2000) and differentiation of fetal hepatocytes (Kamiya et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Like other IL-6 type cytokines, OSM plays a crucial role in inflammation, immune response, hematopoiesis, liver and neuronal regeneration (Kamiya et al, 1999;Chen and Benveniste, 2004). Specific effects of OSM include the renal inflammatory response (Baumann et al, 2000) and differentiation of fetal hepatocytes (Kamiya et al, 1999). Moreover, OSM is the most active IL-6 type cytokine to inhibit, via STAT3 and p21 WAF1 , the proliferation of various solid tumor cell lines such as osteosarcoma (Bellido et al, 1997, melanoma, hepatoma and breast cancer (Grant and Begley, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The hepatoblasts migrate in cord-like structures and the endothelial cells associate with them to form capillary-like structures between them [Duncan, 2003]. Hematopoietic cells migrate into the liver bud during E12 and further proliferate there, apparently emitting a growth signal for the liver [Kamiya et al, 1999]. Numerous signal transduction molecules and transcription factors are than needed for the continued growth of the fetal liver and to prevent apoptosis [Zaret, 2002;Duncan, 2003].…”
Section: Structure and Development Of The Liver In Rodents And Humansmentioning
confidence: 99%
“…HGF supports fetal hepatocytes during mid-stage hepatogenesis and it was shown that mice lacking HGF had reduced sized embryonic liver [Maina et al, 1996]. OSM is produced by the hematopoietic cells and induces the maturation of fetal hepatocytes [Kamiya et al, 1999]. Dexamethasone is a synthetic glucocorticoid hormone active in induction of enzymes concerned in gluconeogenesis in the liver such as phosphoenolpyruvate carboxykinase (PEPCK), tyrosine aminotransferase (TAT), and others and thus it was usually added last to the culture media [McGrane et al, 1990].…”
Section: Embryonic Stem Cells and Hepatocytesmentioning
confidence: 99%